2015
DOI: 10.1053/j.gastro.2014.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in RAD21 Disrupt Regulation of APOB in Patients With Chronic Intestinal Pseudo-Obstruction

Abstract: Background & Aims Chronic intestinal pseudo-obstruction (CIPO) is characterized by severe intestinal dysmotility that mimicks a mechanical sub-occlusion with no evidence of gut obstruction. We searched for genetic variants associated with CIPO to increase our understanding of its pathogenesis and indentify potential biomarkers. Methods We performed whole-exome sequencing of genomic DNA from patients with familial CIPO syndrome. Blood and lymphoblastoid cells were collected from patients and controls (individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 42 publications
(57 reference statements)
3
65
0
1
Order By: Relevance
“…Moreover, unlike patients with the congenital neuropathy, Hirschsprung disease, 42,43 CIPO patients with degenerative myopathy are variable in age. 3 The colonic myopathy in Nup35-mutant mice was not apparent at birth and so is consistent with the degenerative myopathy seen in a subpopulation of CIPO patients.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Moreover, unlike patients with the congenital neuropathy, Hirschsprung disease, 42,43 CIPO patients with degenerative myopathy are variable in age. 3 The colonic myopathy in Nup35-mutant mice was not apparent at birth and so is consistent with the degenerative myopathy seen in a subpopulation of CIPO patients.…”
Section: Discussionsupporting
confidence: 65%
“…3 Mutations linked to CIPO in humans are often associated with neuropathy rather than myopathy (eg, SOX10 and RAD21), 3,12 and so are unlikely to be related to the Nup35-mutant phenotype. The mechanism by which NUP35 deficiency triggers smooth muscle myopathy thus remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A homozygous pathogenic variant in the RAD21 gene was reported in one consanguineous family. 18 4/28 of our cohort and 15/27 in the report by Wangler et al 4 were found to harbor an ACTG2 pathogenic variant. The difference between these two randomly collected cohorts remains unexplained, but may reflect inaccurate clinical diagnoses.…”
Section: Discussionsupporting
confidence: 42%
“…Genome-wide linkage analysis and homozygosity mapping approach identifi ed a maximum multipoint lod score of 5.01 in a critical interval of about 13 Mb between D8S1830 and D8S1799 on the chromosome 8q23-q24 (Deglincerti et al 2007 ). Using whole exome sequencing analysis we have shown a novel mutation in the RAD21 gene, cosegregating with the disease phenotype in this family (Bonora et al 2015 ). Therefore, it is clear that even severe forms of ENs show a high degree of genetic heterogeneity, hindering the identifi cation of the molecular causes and of the deranged molecular pathways shared by the different affected individuals.…”
Section: Ens With Genetic Abnormalitiesmentioning
confidence: 88%